2022
DOI: 10.1136/bmjopen-2021-058270
|View full text |Cite
|
Sign up to set email alerts
|

Spatial scenery of congenital syphilis in Brazil between 2007 and 2018: an ecological study

Abstract: ObjectiveTo analysis the epidemiological scenery of the congenital syphilis (CS) in Brazil employing spatial analysis techniques.DesignEcological study.SettingsThis study was conducted in BrazilSampleA total of 151 601 CS cases notified to the Diseases and Notification Information System from 2007 to 2018 from children aged 0–23 months and born from mothers living in Brazil were included in this study.Primary outcome measuresThe CS incidence rates were calculated by triad (2007–2010, 2011–2014 and 2015–2018) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 29 publications
(19 reference statements)
0
5
0
3
Order By: Relevance
“…Previous research has used spatial analysis to map disease distribution (eg, for multiple sclerosis [ 7 ], HIV [ 8 ], and COVID-19 [ 9 ]), and spatial analysis could also guide health strategies against syphilis [ 10 ], which has a high incidence and represents a problem for public health worldwide, especially in Latin America, Africa, and Asia [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has used spatial analysis to map disease distribution (eg, for multiple sclerosis [ 7 ], HIV [ 8 ], and COVID-19 [ 9 ]), and spatial analysis could also guide health strategies against syphilis [ 10 ], which has a high incidence and represents a problem for public health worldwide, especially in Latin America, Africa, and Asia [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A previous study used spatial analysis to assess the epidemiological status of congenital syphilis in Brazil and found that the most affected municipalities were those with a large migratory flow, those bordering other countries, and those with many tourists [ 10 ]. Clusters of congenital syphilis were even identified in municipalities with prenatal care [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…de SC por quadriênio para cada região brasileira, observa-se que na Região Nordeste, houve aumento na taxa de incidência nos estados do Rio Grande Norte e Ceará em todo período analisado, bem como nos munícipios do interior de Sergipe, Piauí, Alagoas e Bahia. 9 Diante dessa elevada prevalência, é notória a dificuldade de enfrentamento da sífilis gestacional no Brasil e no mundo. A baixa adesão ao tratamento da gestante, a não adesão ao tratamento pelo parceiro e a vulnerabilidade social elavam o risco de transmissão vertical em cerca de 70% a 100% dos casos notificados.…”
unclassified
“…É fato que o pré-natal é capaz de fazer o reconhecimento precoce da sífilis em gestantes e é um meio que viabiliza uma progressão mais favorável dos casos de SC (SOARES; AQUINO, 2021;e congênita continuam crescendo continuamente a cada ano, o que nos leva a concluir que "apesar do aumento das coberturas de pré-natal, ainda se observa uma baixa efetividade dessas ações para a prevenção da SC"(ARAÚJO et al, 2020, p. 479-486). Em outras palavras, apesar da grande cobertura do pré-natal em território nacional, a qualidade desse serviço no Brasil ainda é baixa(SEABRA et al, 2022).É necessário que esteja bem claro que a falha na assistência pré-natalseja por realização inadequada, tardia ou incompletairá interferir tanto na execução de um diagnóstico correto e precoce da sífilis, como em um tratamento conveniente e em tempo propício. Há forte associação entre casos de sífilis congênita e assistência pré-natal inadequada(VALENTIM et al, 2022; DOMINGUES et al, 2021).…”
unclassified